Identification of the gene encoding the mitochondrial elongation factor G in mammals. - Barker, C (1993)
Protein synthesis in cytosolic and rough endoplasmic reticulum associated ribosomes is directed by factors, many of which have been well characterized. Although these factors have been the subject of intense study, most of the corresponding factors regulating protein synthesis in the mitochondrial ribosomes remain unknown. In this report we present the cloning and initial characterization of the gene encoding the rat mitochondrial elongation factor-G (rEF-Gmt). The rat gene encoding EF-Gmt (rMef-g) maps to rat chromosome 2 and it is expressed in all tissues with highest levels in liver, thymus and brain. Its DNA sequence predicts a 752 amino acid protein exhibiting 72% homology to the yeast Saccharomyces cerevisiae mitochondrial elongation factor-G (YMEF-G), 62% and 61% homology to the Thermus thermophilus and E. coli elongation factor-G (EF-G) respectively and 52% homology to the rat elongation factor-2 (EF-2). The deduced amino acid sequence of EF-G contains characteristic motifs shared by all GTP binding proteins. Therefore, similarly to other elongation factors, the enzymatic function of EF-Gmt is predicted to depend on GTP binding and hydrolysis. EF-Gmt differs from its cytoplasmic homolog, EF-2, in that it contains an aspartic acid residue at amino acid position 621 which corresponds to the EF-2 histidine residue at position 715. Since this histidine residue, following posttranslational modification into diphthamide, appears to be the sole cellular target of diphtheria toxin and Pseudomonas aeruginosa endotoxin A, we conclude that EF-Gmt will not be inactivated by these toxins. The severe effects of these toxins on protein elongation in tissues expressing EF-Gmt suggest that EF-Gmt and EF-2 exhibit nonoverlapping functions. The cloning and characterization of the mammalian mitochondrial elongation factor G will permit us to address its role in the regulation of normal mitochondrial function and in disease states attributed to mitochondrial dysfunction.